Drug-induced thrombotic microangiopathy: An updated review of causative drugs, pathophysiology, and management - Mazzierli, Tommaso; Allegretta, Federica; Maffini, Enrico; Allinovi, Marco (Frontiers in Pharmacology, 2023)
Drug-induced thrombotic microangiopathy (DITMA) represents 10-13% of all thrombotic microangiopathy (TMA) cases and about 20-30% of secondary TMAs, just behind pregnancy-related and infection-related forms. Although the list of drugs potentially involved as causative for TMA are rapidly increasing, the scientific literature on DITMA is quite scarce (mostly as individual case reports or little case series), leading to poor knowledge of pathophysiological mechanisms and clinical management. In this review, we focused on these critical aspects regarding DITMA. We provided an updated list of TMA-associated drugs that we selected from a scientific literature review, including only those drugs with a definite or probable causal association with TMA. The list of drugs is heterogeneous and could help physicians from several different areas to be familiar with DITMA. We describe the clinical features of DITMA, presenting the full spectrum of clinical manifestations, from systemic to kidney-limited forms. We also analyze the association between signs/symptoms (i.e., malignant hypertension, thrombocytopenia) and specific DITMA causative drugs (i.e., interferon, ticlopidine). We highlighted their multiple different pathophysiological mechanisms, being frequently classified as immune-mediated (idiosyncratic) and dose-related/toxic. In particular, to clarify the role of the complement system and genetic deregulation of the related genes, we conducted a revision of the scientific literature searching for DITMA cases who underwent renal biopsy and/or genetic analysis for complement genes. We identified a complement deposition in renal biopsies in half of the patients (37/66; 57%), with some drugs associated with major deposits (i.e. gemcitabine and ramucirumab), particularly in capillary vessels (24/27; 88%), and other with absent deposits (tyrosine kinase inhibitors and intraocular anti-VEGF). We also found out that, differently from other secondary TMAs (such as pregnancy-related-TMA and malignant hypertension TMA), complement genetic pathological mutations are rarely involved in DITMA (2/122, 1.6%). These data suggest a variable non-genetic complement hyperactivation in DITMA, which probably depends on the causative drug involved. Finally, based on recent literature data, we proposed a treatment approach for DITMA, highlighting the importance of drug withdrawal and the role of therapeutic plasma-exchange (TPE), rituximab, and anti-complementary therapy.